Phytonutrient Composition of Bryophyllum pinnatum “(Lam.) Oken” Aqueous Leaf Extracts - Jimi-Olatunji, D. A.; Olumide, M. D.; Tayo, O. G.; Akintunde, A. O. (ADAN JOURNAL OF AGRICULTURE, 2026)
Herbs have been used in folk and ethno-veterinary medicine, long before their therapeutic effects were scientifically linked to bioactive phytochemicals. This study was conducted to compare the phytonutrient compositions of unfiltered Bryophyllum pinnatum aqueous leaf extracts (UFBPALE) and filtered Bryophyllum pinnatum aqueous leaf extracts (FBPALE). Fresh Bryophyllum pinnatum leaves of about 60 g were blended with 300 mL of water for three (3) minutes. The extract was divided into two portions: the first portion, UFBPALE, was stored in a sterile bottle without further processing, while the second portion, FBPALE, was filtered through Whatman No. 1 filter paper before being stored in a sterile bottle. Both extracts were subsequently analyzed in the laboratory for their phyto-constituents. Data were analyzed using SPSS Version 20.0 and expressed as Mean ± SD of three replicates determinations while independent t-test was used to test for the significance. The proximate results showed a significant difference (p<0.05) in lipids, ash and crude fibre while phenol and alkaloids in the phytochemical composition were significantly different (p<0.05) with UFBPALE containing higher levels of phenols (9.80 g/100g) and alkaloids (8.40 g/100 g) than FBPALE, which had 9.10 g/100g and 7.10 g/100 g, respectively. The amino acid profile shows no significant differences with the exception of arginine, alanine, aspartic acid and threonine. Conversely, all the vitamins and mineral were significantly different (p<0.05) except zinc. Vitamins B₁, B₂, B₃, and C were higher in FBPALE than in UFBPALE while the minerals were higher in UFBPALE with the exception of potassium. The findings showed that despite minor differences in composition, unfiltered and filtered Bryophyllum pinnatum extracts contain comparable phyto-nutrients and both have potentials for use in livestock production.